Pilots' Estimation of Altitude of a Small Unmanned Aircraft System (sUAS). (September 2018) - Lennertz, Tracy; Sparko, Andrea L.; Cardosi, Kim; Yost, Alan; Kendra, Andrew; Lu, Jason; Sheridan, Tom
Small unmanned aircraft system (sUAS) operations are growing at a rapid rate, with an increasing number of civilian operations. Currently, the Federal Aviation Administration permits both hobbyist and commercial operations. The requirements for the operations differ; for commercial operations, the sUAS must generally be flown under 400 feet. Past data indicate that operators are poor at judging the altitude of sUAS, and there is variability in the altitude information that is presented to the operator. Here, we examined the ability of commercial and hobbyist sUAS pilots to estimate the altitude of their ownship during a realistic flying task. Participants flew a DJI Phantom 4 Pro to three prescribed altitudes: 50 feet, 200 feet, and 350 feet. In each trial, the participant flew the sUAS from its starting point, hovered at what he or she estimated to be the prescribed altitude, and took a photo of a target. Results indicated that participants' altitude estimates were below the prescribed altitude of 50 feet 52% of the time, and they were below prescribed altitudes of 200 feet and 350 feet 89% of the time. Despite differences in background, performance did not differ between hobbyist and commercial pilots. Variability in absolute and barometric measurements of altitude was also observed. Taken together, the results suggest that sUAS pilots, regardless of their experience, are poor at judging the altitude of their ownship—especially at higher altitudes. The variability in performance and altitude measurements indicates that pilots need a reliable and standard way to measure the altitude of their ownship, especially given the increasingly complex environments in which sUAS intend to fly.